Dendroclimatic analysis of common pine (Pinus sylvestris L.) on the SNNP “Burabay”territory - Mapitov, N.; Kassanova , A.; Ibraeva , K.; Yestayeva , M.; Daulet , Z. (Fundamental and Experimental Biology, 2025)
The study aims to obtain new data on the chronology of Pinus sylvestris L. under arid conditions in the forest[1]steppe zone of northern Kazakhstan, specifically in the northern part of the SNNP “Burabay” territory. Two sites were selected to compare how different factors influence wood growth. Analysis of the generalised tree[1]ring chronologies revealed a substantial number of trees in the study area that are between 170 and 220 years old. First-order autocorrelation values ranged from 0.68 to 0.78. The sensitivity coefficient indicated the pres[1]ence of a weak climatic signal. Short-term climate projections suggest a slight increase in temperature and a decrease in warm-season precipitation over the next 10 years.